Wear and heat shock resistance of Ni-WC coating on mould copper plate fabricated by laser - Yu Liu; Tianhao Xu; Ying Liu; Yali Gao; Chi Di (Journal of Materials Research and Technology, 2020)
A Ni-WC coating was fabricated successively on a copper substrate by laser. The microstructure, hardness and wear resistance were investigated. The thickness of Ni-WC coating was 0.65 mm and average hardness of strengthening layer was 667HV0.1, which was approximately 7.8 times higher than the hardness of copper substrate. The wear volume of Ni-WC coating was only 0.014 mm3, which was only 1.02% wear volume of copper substrate. The decrease in wear volume was mainly due to presence of reinforced phases, such as γ-Ni, Cr0.19Fe0.7Ni0.11, M7C3, M23C6 and WC. In addition, there was no coating peeled off after 100 times trials of heat shock resistance experiment at 800℃. The experimental results show that this Ni-WC coating has a good metallurgical bonding strength and hardness, and it also has good wear resistance and high temperature property, which is helpful to improve the service life of mould copper plate.